LAYOUT DESIGN WITH WAREHOUSE SHARED STORAGE METHOD - Firman Ardiansyah Ekoanindiyo (Jurnal Ilmiah Dinamika Teknik, 2011)
Storage in the manufacturing industry is an important role, it may not yield immediate distribution to all its customers. Conditions warehouse layout that is not based on a comprehensive layout design can lead to inefficiencies in time retrieval and storage of materials and material handling operators difficult due to limited warehouse. In the effort to reduce disk space requirements on a dedicated storage, some warehouse managers use a variety of dedicated storage where the placement of the final product regulated more carefully. Shared storage can be considered as a system of moving goods quickly to a product, if each pallet warehouse filled in a different area from time to time. Keywords: Storage, Warehouse, Shared Storage